Pulsed nonlinear acoustic fields from clinically relevant sources: numerical calculations and experiments results - WÓJCIK, Janusz; KUJAWSKA, Tamara; NOWICKI, Andrzej (Archives of Acoustics, 2008)
The goal of this work was to verify experimentally the applicability of the recently developed Time-Averaged Wave Envelope (TAWE) method [1] as a tool for fast prediction of pulsed nonlinear pressure fields from focused nonaxisymmetric acoustic sources in attenuating media. The experiments were performed in water at the fundamental frequency of 2.8 MHz for spherically focused (focal length F = 80 mm) square (20x20 mm) and rectangular (10x25 mm) sources similar to those used in the design of 1D linear arrays operating with ultrasonic imaging systems. The experimental results obtained with 10-cycle tone bursts at three different excitation levels corresponding to linear, moderately nonlinear and highly nonlinear propagation conditions (0.045, 0.225 and 0.45 MPa on-source pressure amplitude, respectively) were compared with those yielded using the TAWE approach. Comparison of the experimental and numerical calculations results has shown that the TAWE approach is well suited to predict (to within [ampersand]plusmn;1 dB) both the spatial-temporal and spatial-spectral pressure variations in the pulsed nonlinear acoustic beams.